Trends in computer science, engineering and information technology first International Conference on Computer Science, Engineering and Information Technology, CCSEIT 2011, Tirunelveli, Tamil Nadu, India, September 23-25, 2011. Proceedings - Nagamalai, Dhinaharan; Renault, Eric; Dhanuskodi, Murugan (Communications in computer and information science, 2011)
This book constitutes the refereed proceedings of the First International Conference on Computer Science, Engineering and Information Technology, CCSEIT 2011, held in Tirunelveli, India, in September 2011. The 73 revised full papers were carefully reviewed and selected from more than 400 initial submissions. The papers feature significant contributions to all major fields of the Computer Science and Information Technology in theoretical and practical aspects.